Feeding Practice with Preventing Stunting on Keluarga Harapan Program Recipients in Pangkajene and Islands Districts - Mardhatillah, Mardhatillah; Sulaiman, Zulkarnain; Febrianti, Devy; Adri, Khaeriyah; Said, Sunandar (Journal of Maternal and Child Health, 2022)
Background: Stunting is a condition where toddlers are shorter in length and height than their age. Percentage of stunting children in Pangkajene and Islands Districts with the highest percentage of 29.10% and the number of PKH recipients in 2019 as many as 16,498. The purpose of this study was to determine the relationship between Feeding Practice and the incidence of stunting on Keluarga Harapan Program recipients in Pangkajene and Islands Districts. Subjects and Method: The type of research used is observational with a cross sectional study design. The independent variable in this study is stunting and the dependent variable are feeding practice, Low Birth Weight and Economic status. The research location was carried out in Pangkajene and Islands Districts. The population in this study was all infants or toddlers from PKH recipient parents in Pangkajene and Islands Districts as many as 2,946 people in 2019 - 2021. The research sample was infants or toddlers from PKH parents who had participated in the Family Development Session as many as 71 people with the purposive method sampling. Primary data was collected using a questionnaire while secondary data was obtained from the social service of Pangkajene and Islands Districts. This study using the chi square test. Results: Incidence of stunting was higher in respondents with irregular feeding practice than in regular feeding practice (OR=0.54; CI 95% 0.33 to 0.91; p=0.024). The incidence of stunting was higher at low birth weight compared to toddlers with normal birth weight (OR= 0.41; CI 95% 0.23to 0.73; p = 0.001). The incidence of stunting is higher in economic status below the provincial minimum wage < Rp. 3,103,800 compared to economic status > Rp. 3,103,800 (OR = 2.25; CI 95% 1.16 to 4.38; p=0.01). Conclusion: Low economic status has a risk of 2.252 times experiencing stunting.